2019
DOI: 10.3389/fimmu.2019.02373
|View full text |Cite
|
Sign up to set email alerts
|

Ureaplasma Urealyticum Infection Contributes to the Development of Pelvic Endometriosis Through Toll-Like Receptor 2

Abstract: Endometriosis is a chronic gynecological disorder, characterized by the presence of ectopic endometrial tissue outside the uterine cavity. Among several hypotheses, Sampson's theory of retrograde menstruation is still applicable. Recent studies have reported the importance of inflammation among endometrial tissue, the peritoneum, and immune cells. However, less is known regarding the role of bacterial infection in the pathophysiology of endometriosis. We hypothesized that Ureaplasma urealyticum infection might… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 67 publications
0
6
0
Order By: Relevance
“…Despite the prevalence of and disablement caused by endometriosis, its pathogenesis remains unknown (100). A lesser known and under-investigated hypothesis proposes that microbes may contribute to endometriosis etiopathology (i.e., "bacterial contamination hypothesis") (101) via an inflammatory response and TLR4 (102-104) and TLR2 activation (104,105). This research is notable in the context of studies on pathogen persistence and pathobionts in infection-associated chronic illnesses and how they may be implicated in multiple pathologies (106-108).…”
Section: Endometriosismentioning
confidence: 99%
“…Despite the prevalence of and disablement caused by endometriosis, its pathogenesis remains unknown (100). A lesser known and under-investigated hypothesis proposes that microbes may contribute to endometriosis etiopathology (i.e., "bacterial contamination hypothesis") (101) via an inflammatory response and TLR4 (102-104) and TLR2 activation (104,105). This research is notable in the context of studies on pathogen persistence and pathobionts in infection-associated chronic illnesses and how they may be implicated in multiple pathologies (106-108).…”
Section: Endometriosismentioning
confidence: 99%
“… 28 UU might activate the immune response in vivo and enhance the chemotaxis and stress effects of inflammatory cells such as neutrophils. 29 For reasons of high cost and low patient compliance and acceptance, we did not investigate sperm DNA fragmentation. This is a major limitation of our study, and we plan to include such an investigation in our future in-depth analysis.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, several in vitro studis have demonstrated that Ureaplasma spp. modulate cytokine [34,35] and proinflammatory responses in a dose-dependent manner [36]. Interestingly, one study indicated that a high load of U. parvum (10 7 CFU/ml) can significantly increase prothrombin/thrombin mRNA expression to promote the onset of PPROM but that a lower load (10 5 CFU/ml) had no significant effect [6].…”
Section: Discussionmentioning
confidence: 99%